Are strategies created differently based upon TMT gender diversity? : Examining the role of TMT gender diversity in strategy work - Cantell, Heidi (My University, 2021)
This thesis explores the role of top management team (TMT) gender diversity in firm’s strategy creation and strategy work. The aim is to explore whether differences exist between different managerial groups in this context. The study is conducted by using a multiple-case research design. The theoretical framework starts with introducing strategy process research stream continuing to strategy-as-practice perspective (SAP), which was applied in this study. Second, existing literature of top management team research is provided to create a basis for studying top management teams. Next, existing literature of TMT diversity is provided continuing to TMT gender diversity related literature. The empirical part of the study was conducted by using a multiple-case research design. The study consisted of three different cases. One, representing TMTs consisting mostly of women, second representing TMTs consisting mostly of men and third diverse group representing TMT consisting half of women and half of men. The data was collected by using a semi-structured interview technique and analyzed by using qualitative content analysis methods. As a result, although cases had many similarities, few differences existed. First, each case described themselves differently from each other by using different adjectives. Slightly more subtle adjectives were used by women compared to men’s more decisive word choices. Second, the differences existed in the participation of personnel in the strategy creation. The findings show that the participation was emphasized the most in the case representing gender diverse TMT in which personnel was strongly engaged with the strategy creation. Findings also indicate that decision-making in homogeneous TMTs, which consists of either men or women stood out more agile compared to diverse case. All cases stood out with their collective way of making decisions. Last, findings also pointed out that all cases utilized many different sources of data for strategic decision-making, emphasizing financial means. In addition, TMTs consisting mostly of women pointed out also the support of feelings and personal beliefs in decision-making.
Keywords: gender; strategy work; leadership (activity); strategies; management teams; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development